Production of Mycoprotein by Fusarium venenatum Growth on Modified Vogel Medium - HOSSEINI, S.M.; KHOSRAVI-DARANI, K.; MOHAMMADIFAR, M.A.; NIKOOPOUR, H. (Asian Journal of Chemistry, 2010)
Fusarium venenatum (ATCC 20334) was used for fungal protein production. Date sugar was selected as a carbon source. An 8 run Plackett-Burman design was used to study the effect of 7 variables i.e., medium components, temperature, incubation time and inoculum condition on biomass and protein production. The most significant parameters were the seed size (10 % v/v) and carbon source concentration (10 g/L), followed by the temperature (28 ºC) and nitrogen source content (3.5 g/L). In the best condition 47.34 % (w/w) crude protein in the dry product was obtained.